THREE-DIMENSIONAL GIS MODELING OF THE STRELTSOVSKAYA CALDERA’S COVER ON THE BASIS OF SURFACE RELIEF AND THE BASEMENT’S TOP DIGITAL MODELS - I. O. NAFIGIN; S. A. USTINOV; V. A. PETROV (Известия высших учебных заведений: Геология и разведка)
Based on the consideration and analysis of different approaches to obtaining data for constructing a digital elevation model and types of  three-dimensional surface representation, the choice of the most  optimum technique for construction and visualization of three- dimensional model of the volcano-sedimentary cover of the  Streltsovskaya caldera in Eastern Transbaikalia has been  substantiated. The creation of such model determines the need for  detection, identification and monitoring of processes, phenomena  and factors of natural and anthropogenic origin at uranium deposits of the same named ore field, which are developed by  underground way in difficult mining and geological conditions. To  solve this problem, modeling of the daylight surface relief and the  basement roof has been carried out on the basis on remote sensing  data, geophysical studies, cartographic materials vectorization and  processing results. The space between the constructed surfaces due  to the algorithm for creating closed framework of surfaces has been  transformed into a new object representing three-dimensional  volumetric model of the caldera volcano-sedimentary cover. The received results allow creating a predictive model of the tectonic and dynamic state of the Streltsovky ore field rock massifs for the deposits development and mine workings design.